International Differences in Multiple Sclerosis Health Outcomes and Associated Factors in a Cross-sectional Survey - Reilly, Grace D.; Mahkawnghta, Awng Shar; Jelinek, Pia L.; De Livera, Alysha M.; Weiland, Tracey J.; Brown, Chelsea R.; Taylor, Keryn L.; Neate, Sandra L.; Jelinek, George A.; Marck, Claudia H. (Frontiers in Neurology, 2017)
Multiple sclerosis (MS) is a major cause of disability and poor quality of life (QOL). Previous studies have shown differences in MS health outcomes between countries. This study aimed to examine the associations between international regions and health outcomes in people with MS. Self-reported data were taken from the HOLISM (Health Outcomes and Lifestyle In a Sample of people with Multiple Sclerosis) online survey collected in 2012. The 2401 participants from 37 countries were categorised into three regions: Australasia, Europe, and North America. Differences were observed between regions in disability, physical and mental health QOL, fatigue and depression, but most of these disappeared after adjusting for socio-demographic, disease, and lifestyle factors in multivariable regression models. However, adjusted odds for disability were higher in Europe (Odds Ratio (OR): 2.17, 95% Confidence Interval (CI): 1.28 to 3.67) and North America (OR: 1.79, 95% CI: 1.28 to 2.51) compared to Australasia. There may be other unmeasured factors that vary between regions, including differences in access and quality of healthcare services, determining disability in MS. When assessing differences in MS health outcomes, lifestyle factors and medication use should be taken into consideration.